Unveiling Emotions. Vol. 3 : Arousal, Display, and Performance of Emotions in the Greek World - Chaniotis, Angelos (Heidelberger althistorische Beiträge und epigraphische Studien, 2020)
Intro -- CONTENTS -- PREFACE -- (Angelos Chaniotis) Display, arousal, and performance of emotions: Introduction -- PART ONE: Emotional Constructions -- (Dimos Spatharas) Projective disgust and its uses in ancient Greece -- (Angelos Chaniotis) Power relations as emotional relations: Hellenistic and Imperial realities and fictions -- (Sophia Kravaritou) Displaying guilt, remorse, and redemption in Greek public contexts -- (Maria G. Xanthou) Isocrates and emotional intelligence theory: from local audience to international politics -- (Vasiliki Giannopoulou) Emotions and politics in Polybios Book Six -- PART TWO: Arousing Emotions -- (Matthew Peebles) Threatening gods for fearful mortals: Weapon-brandishing divinities in ancient Greek art -- (John Tait) Examining the exploitation of the emotion in Demotic Egyptian letter-writing -- (Vasiliki Giannopoulou) Autopatheia: personal empathic experience, didactic mission, and readershaped empathy in Polybios -- (Elizabeth Potter) Learning emotion: the progymnasmata and the rhetorical education of the ancient audience -- (Bernhard Palme) Emotional strategies in petitions of Dioskoros of Aphrodito -- PART THREE: Performing Emotions -- (Marco Fantuzzi) Describing images, connoting feelings: choral ecphrasis in Euripides -- (Helen Slaney) Repetition makes it tragic: emotion in ancient pantomime -- (Elizabeth Potter) Emotion, performance, and persuasion in Philostratos' Lives of the Sophists -- (Dimitris Karambelas) Emotions in court: judicial display and psychic audience between the Imperial period and Late Antiquity -- (David Frankfurter) Desperation and the magic of appeal: representation of women's emotion in magical spells and ritual figurines -- INDEX -- CONTRIBUTORS.